Annelid Biodiversity In Dead Corals Against Pollution In Tarahan Island - Baretta Ari Nauli; Zahra Amalia Putri; Rita Arisma Banjarnahor; Habil Hisyam; Bagas Septian Pratama; A'tha Dhafa Bayu Setya; Moch Saad; Prakas Santoso; Afifah Nurazizatul Hasanah (Grouper, 2025)
Tarahan Island is one of the small islands located in the waters of Banten Bay, Banten Province. This study aims to determine the cryptic organisms found on dead corals and determine the level of seawater pollution with TSS, BOD, COD parameters used as variables for assessing the status of water pollution in Tarahan Island, Banten. The method used in this research is using Purposive Sampling location determination. Data collection was carried out on March 26, 2025 to May 15, 2025 on Tarahan Island. Based on the results of the study found 42 individuals of the phylum Annelida. The most common species found was Alitta Succinea. The results of TSS research showed an average concentration of 377.77778 mg/L and BOD had an average concentration of 0.616667 mg/L.